Wspomnienia polskich dyplomatów jako źródło w badaniu stosunków polsko-rosyjskich po 1989 roku - Urbański, Filip (Acta Polono-Ruthenica, 2018)
The article describes the problem of using the autobiographical documents of polish ambassadors in Russia after 1989 as a source in analysis of Poland-Russia relations. The author affirms that memoires and extended interviews of former diplomats could be useful in process of reconstruction of past political events. Nonetheless all researchers have to remember that as all sources the autobiographical documents should be subjected to strict procedure of research because they are highly subjective. As examples the author used memoires Mr. Stanisław Ciosek and extended interviews Mr. Stefan Meller and Mr. Jerzy Bahr.